Respostas
respondido por:
0
x+y= 80
x-y= 56
logo x=80-y
substituindo na segunda eq.
80-y=56
-y=56-80
-y=-24 *(-1)
y=24
para achar o x
x+24=80
x=80-24
x=56
:))
x-y= 56
logo x=80-y
substituindo na segunda eq.
80-y=56
-y=56-80
-y=-24 *(-1)
y=24
para achar o x
x+24=80
x=80-24
x=56
:))
rodrigoduvida:
Obrigado
respondido por:
2
x+a=80 --> 56+a+a=80
2a=80-56
a= 12
x-a=56
x=56+a
x= 56+12
x= 68
2a=80-56
a= 12
x-a=56
x=56+a
x= 56+12
x= 68
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás